High-Sensitivity Cardiac Troponin Predicts Major Cardiovascular Events in Diabetic Patients With Critical Limb Ischemia and Foot Lesions - Cimaglia, Paolo; Dalla Paola, Luca; Carone, Anna; Scavone, Giuseppe; Manfrini, Marco; Brogneri, Simona; Tenti, Elena; Pavasini, Rita; Bernucci, Davide; Passarini, Giulia; Vitali, Francesco; Gaudenzi, Eleonora; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background. Diabetic patients with critical limb ischemia (CLI) and foot lesions show a poor prognosis. Optimal risk stratification to guide tailored intervention is still uncertain. Aim of the present study was to assess the prognostic role of high-sensitivity cardiac troponin T (hs-TnT) in such a high-risk population. Methods and Results. Clinical, laboratory and interventional data, as well as the SPINACH score, were collected. Hs-TnT was measured at hospital admission. All patients were followed-up for at least one year. The primary endpoint was the cumulative occurrence of major cardiovascular events (MACE, all-cause death, myocardial infarction or stroke). The secondary endpoint was all-cause mortality. Overall, 618 patients were included and followed for a median of 981 [557-1325] days. Diagnosis of coronary artery disease (CAD) was established in 270 (43.7%) patients. Median hs-TnT at admission was 31 [20-59] ng/L, with 525 (85%) patients over the upper reference limit. Hs-TnT values was significantly higher in patients with established CAD (39 vs 29 ng/L, p<0.01). Hs-TnT was an independent predictor of MACE (HR 2.440, 95%CI 1.706-3.489, p<0.001). The best cut-offs were 40 ng/L (AUC 0.711) for patients with established CAD, and 25 ng/L (AUC 0.725) for those without. Hs-TnT emerged also as an independent predictor of all-cause mortality. The addition of hs-TnT improved prognostic value of the SPINACH score. Conclusions. Hs-TnT is a powerful biomarker for prognostic stratification of diabetic CLI patients with foot lesions. This is confirmed independently to CAD diagnosis and permits the identification of higher risk patients requiring tailored intervention.